"That's the Beauty of It": Practitioners Describe the Affordances of Direct to Consumer Tele-Mental Health. Issue 4 (October 2021) - Goldkind, Lauri; Wolf, Lea
Tele-mental health, or the provision of remote counseling services, has been available for decades. This qualitative study uses the framework of affordances, derived from Gibson, to examine what social work practitioners working on direct to consumer tele-mental health (DTCTMH) platforms are discovering about the features, benefits, and constraints of virtual therapy. An interpretive phenomenological approach was employed to document the lived experiences of social workers who practice in this manner. According to the practitioners interviewed, for a subset of individuals seeking treatment, DTCTMH can offer meaningful interpersonal interaction that confers benefit. Key affordances include accessibility, anonymity, meaningful work, autonomy, lifelong learning, and access by new populations. Practitioners simultaneously acknowledge the ethical complexities and structural challenges of DTCTMH practice. The article concludes with suggestions for future research, policy, and practice.